Pengetahuan Ibu Post Partum dengan Pantang Makanan Selama Masa Nifas - Yulli Fety; Sri Mulyani; Lisnawati Lisnawati; Rida Aprianti (Journal of Telenursing (JOTING), 2023)
This study aims to determine the relationship between postpartum mothers' knowledge and food abstinence during the postpartum period. This research method uses a quantitative research type with a cross sectional study design. The population in this study was 55 people, with a simple random sampling technique with a sample size of 48 people. The analysis method uses statistical tests, namely the chi square and Cramer's tests. The results of this study indicate that the knowledge of post partum mothers is moderately related to abstaining from food during the postpartum period. The value obtained is (X2 Hit= 5.802 > North Wowonii District, Konawe Islands Regency. Keywords: Postpartum Period, Food Abstinence, Knowledge